Recent advances on pumping schemes for mid-IR PCF lasers - Stefano Taccheo (Proc. SPIE 10100, Optical Components and Materials XIV, 1010002 (February 16, 2017); doi:10.1117/12.2251710, 2017)
The design of two pumping schemes for mid-IR lasers based on photonic crystal fibers (PCFs) is illustrated. The PCFs considered in both pumping schemes are made of dysprosium-doped chalcogenide glass Dy3+:Ga5Ge20Sb10S65. The two optical sources are accurately simulated by taking into account the spectroscopic parameters measured on a rare earth-doped glass sample. A home-made numerical model based on power propagation equations and solving the ion population rate equations of the rare earth is developed and employed to perform a feasibility investigation. The first pumping scheme is based on optical power pumping at 1700 nm wavelength and allows beam emission close to 4400 nm wavelength, the efficiency is increased till about η = 22% by integrating a suitable optical amplifier after the laser cavity. The second pumping scheme exploits two pump beams at the wavelengths close to 2800 nm and 4100 nm and enables a laser emission close to 4400 nm wavelength with an efficiency higher than η = 30%. Both these sources could promote a number of promising applications in different areas such as satellite remote sensing, laser surgery, chemical/biological spectroscopy and mid-IR optical communication. © (2017) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE).